Vegetative Propagation of Sentang (Azadlrachta Excelsa (Jack) Jacobs) by Rooting of Cuttings - Choummaravong, Somphou (1998)
The supply of sentang (Azadirachta excelsa) seeds is limited due to the irregularity of flowering and fruiting and the difficulty of storing seeds for a long period. Therefore, this study examined the possibility of raising planting stock of sentang using cuttings. It involved determination of coppiceability at different stump heights (30, 60 and 100 cm), followed by rooting of these coppices. Also seedlings of two different ages were included in the rooting experiment. Factors such as cutting positions (terminal, middle and basal), as well as different hormonal treatments (control; IBA 50 µg, 100 µg, 150 µg; NAA 100 µg, 150 µg; Seradix 2; and their combinations between IBA 100 µg and NAA 50 µg) were included in this experiment. Results indicated that 60 cm stumps gave the best survival percentage (96.9%) with the best coppiceability in terms of sprout number production (9). However, the best coppiceability in terms of shoot length (39.6 cm) and diameter (0.7 cm) was recorded in the 100 cm stumps. Generally, terminal position was found to be the best cutting position for both plant sources (coppices and seedlings) for survival and rooting percentages. Hormonal application gave a significant effect at P ≤ 0.05 on rootability of cuttings. The highest rooting ability (73.3%) was obtained from terminal cuttings of 23 month-old from FRIM seedlings when treated with 100 µg IBA. In contrast, survival percentages of only 20% and 50% were obtained from terminal cuttings of 34 month-old seedlings and 4 month-old coppices treated with Seradix 2 respectively. In addition, the 3 week-old coppice cuttings were also tried to further determine whether rootability could be improved and results indicated that single-node coppice cuttings from 30 cm stumps gave an 80% survival, followed by the 60 and 100 cm stumps which recorded similar survival percentages of 47%. Generally, the rooting ability recorded was relatively low i.e. 36%, 18% and 11 % from 30, 60 and 100 cm stumps respectively.